UMP launches alumni card as a token of gratitude - Mimi Rabita, Abdul Wahit (2020)
Gambang 19 October 2020 - Universiti Malaysia Pahang (UMP) launched an alumni card for all its alumni by offering various benefits as a token of gratitude.